PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS AUGMENTED REALITY PADA MATERI TOPOLOGI JARINGAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X TJKT SMK NEGERI 1 KUPANG - Angelina Heleni Perada Liat; Maria Magdalena Beatrice Sogen; Diana Yanni Ariswati Fallo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This thesis was conducted based on the problem that the learning process in the subject of Basic Computer and Telecommunication Network Engineering at Class X TJKT of SMK Negeri 1 Kupang still relies on conventional learning methods, causing difficulties for students in understanding abstract concepts of network topology and resulting in low learning engagement and varied learning outcomes. This research aims to develop an Augmented Reality-based learning media on network topology materials and to determine its effectiveness in improving student learning outcomes. This thesis employed a Research and Development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The media was developed using Unity 3D and Vuforia to present interactive three-dimensional visualizations of network devices and learning materials. Data collection techniques included observation, interviews, questionnaires, tests, and documentation. The developed media was validated by media and material experts before implementation in the learning process. The findings indicate that Augmented Reality-based learning media can support a more interactive, engaging, and contextual learning experience, helping students understand network topology concepts more effectively and contributing to improved student learning outcomes.